Even Intensity and Implementation of Fuzzy Intrinsic Edge-Magic Graphs - Kaliraja, M.; Sasikala, M. (Communications in Mathematics and Applications, 2024)
A graph labelling is an assignment of integers to the vertices or edges, or both under certain restrictions. A fuzzy graph \(G\) is said to be intrinsic edge-magic if it satisfies the intrinsic edge-magic labelling with intrinsic constant \(λ _{c}=σ (v_{i}) +μ (v_{i}v_{j})+σ (v_{j})\), for all \(v_{i}, v_{j} \in V\). In this article, we introduce the even intensity of intrinsic edge magic graph and the application of fuzzy intrinsic edge magic graph is illustrated with suitable example.